Risk Factors of Type 2 Diabetes Mellitus in Hospital of Bengkulu City, Indonesia: Case Control Study - Agung Sutriyawan1 , Tenike G Miranda2 , Hairil Akbar3 , Riswan4 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Background: The prevalence of diabetes mellitus is currently increasing and is an important cause ofpremature death and disability. Insulin resistance in people with type 2 diabetes mellitus is caused by multiplefactors such as non-modifiable factors and modifiable factors. Objectives: assess the relationship of factorscan not be modified and factors can be modified with the incidence of type 2 diabetes mellitus. Methods:This is a case control study. Samples taken based on several criteria, namely: 1) patients aged ? 18 years,2) patients can communicate smoothly. Risk factors were analyzed using the chi-square test, knowing themagnitude of the risk using the Odds ratio (OR). Results: variables related to type 2 diabetes mellitus wereage (p = 0.019), OR = 2.5 (1.2-5.2), family history of diabetes (p = 0.007), OR = 2.9 (1, 3-6.1), body massindex (BMI) (p = 0.001), OR = 3.2 (1.6-6.5), high sugar diet (p = 0,000), OR = 4.2 (2.0 -8.6), low fiber diet(p = 0.018), OR = 2.5 (1.2-5.4), and physical activity (p = 0.000), OR = 7.1 (3.0- 16.6). Conclusion: Riskfactors proven to be related to type 2 diabetes mellitus are age, family history of diabetes, BMI, high sugardiet, low fiber diet, and physical activity. While gender, central obesity and smoking cannot be proven to berisk factors for type 2 diabetes mellitus. Physical activity is a major risk factor for type 2 diabetes mellitus,with a 4 times greater risk for those who lack physical activity